Association of Customer Satisfaction with Store Environment: A Study on Bhat-Bhateni Super Market and Departmental Store - Maharjan, Sarita (Nepalese Journal of Management Science and Research, 2019)
This paper aims at analysing the relationships between store environment and customer satisfaction of Bhat-Bhateni Supermarket and Department Store. Descriptive and analytical research designs were used in this study. Judgemental sampling technique was used to collect opinion survey data through structured questionnaire. Out of 150 questionnaires distributed to customers of Bhatbhateni Super Stores under Bhat-Bhateni Supermarket and Department Store in Kathmandu valley, only 60.61 percent of them were found practical. Compare mean test and Gamma test are used to analyse the association between customer satisfaction and store environment at Bhabhateni Super Stores. Compare means test shows that only customers’ perceptions on employees of Bhatbhateni Super Stores are different by gender. Gamma coefficients show that customer satisfaction has a significant positive association with music, lighting, assortment, interior design and employees except layout. Store environment plays an important role in business. Friendly store environment could be a good factor for supermarket to enhance customers’ satisfaction level.